Suspended sediment concentration measurement based on optical fiber technology. (7th June 2019) - Wang, Rui; Yu, Guoliang
Abstract: A novel approach based on optical fiber technology was presented to measure suspended sediment concentration (SSC) in water and A turbidimeter prototypes with a range of propagation lengths was developed in order to test the effect of that variable on accuracy in this study. A series of experimental runs were performed with natural sediments uniformly distributed in water to test the relationship between SSCs, the intensity of the reflected light and the incident light. The detected voltage collected by a modern measurement was introduced as the parameter to characterize the intensity of the light which was confirmed to increase with the sediments added in the case of low SSCs, so it was thought to be useful for measuring the unknown SSCs. The test results indicated that this optical fiber turbidimeter had good stability and sensitivity which could not be affected by water flow disturbance and the measurement range of SSC was determined by the particle size. It was worth noting that an inflection point would appear in the curve of SSCs-Detected voltage as the increase of the SSC and the value of SSC at the inflection point in terms of 10 g l −1 was close to the value of median particle size in terms of µm. Before the inflection point, and there was a positive logarithmic relationship between SSCs and the detected voltage. On the premise of the same SSCs, the detected voltage decreases with the increase of the median particle size. After the inflection point, the SSC is negatively correlated with the voltage value, but the correlation is unstable due to the difference in the particle size. Finally, according to the scattering and absorption principle of light, the calibration of this optical fiber turbidimeter was discussed. The data processing of the measurement is simple and fast, and the density value is directly readable.